Integrasi MATLAB dalam E-Modul Fisika Statistik Berbasis Heyzine Flipbook: Persepsi Mahasiswa terhadap Bahan Ajar Interaktif - Riswanty Roman Purba; Sri Purwaningsih; Neneng Lestari (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Statistical physics is one of the courses that contains abstract concepts and complex mathematical representations, requiring teaching materials that can support students' conceptual understanding through visualization and simulation. This study aims to develop a statistical physics electronic module based on Heyzine Flipbook assisted by Matlab and to determine students' perceptions of its use on the topics of distribution functions and statistical interpretation of entropy. This study employed the Research and Development (R&D) method using the 4D development model, which consists of the define, design, develop, and disseminate stages. The research subjects were 23 students of the Physics Education Study Program who had completed the statistical physics course. Data were collected through media expert validation sheets, material expert validation sheets, and student perception questionnaires. The results of media expert validation obtained a percentage of 85.53% in the very good category, while material expert validation obtained a percentage of 100% in the very good category. Student perceptions yielded an average score of 3.3 with a percentage of 84%, which was categorized as very good. The developed e-module integrates learning materials, graphical visualization, and Matlab-based simulations to support the presentation of statistical physics concepts. The findings show that the e-module is feasible for use as a digital teaching material and can support students in understanding the relationship between mathematical representations and the physical interpretation of statistical physics concepts. Therefore, the Heyzine Flipbook-based statistical physics e-module assisted by Matlab can be used as an alternative digital teaching material in statistical physics learning.